Investigating differential nutritional and productivity impacts of improved data, policy and accountability mechanisms in Africa’s middle and low-income countries - Matchaya, Greenwell C.; Greffiths, Ikhothatseng Jacob (Springer, 2025)
Africa’s agricultural transformation is on-going but its pace is slow, which is why African Heads of State launched the Comprehensive African Agriculture Development Program (CAADP) in 2003 to speed up agricultural transformation. This study examines the differential effects of improved data and accountability systems under the CAADP program in 40 African countries over the period 2008–2021 on reported mortalities attributable to poor nutrition and productivity. The paper uses a relatively larger sample size of countries and longer periods, thereby providing better clarity on the issues as compared to previous studies Using econometric analysis techniques, the results revealed that nutrition related mortality is significantly negatively related to productivity measures, good policy implementation and evidence reliance scores implying that improvements in these variables improve nutritional outcomes. Mutual accountability processes significantly influence investment decisions,which in turn affect productivity and nutritional outcomes. The results also indicated that a 1% increase in the mutual accountability scores is associated with a 0.5% increase in the size of the agriculture sector for the low-income countries and it is also associated with a 0.3% increase in the share of agriculture employment in the middle-income countries. This paper provides useful information to stakeholders who are currently supporting the CAADP to achieve food security and nutrition. There is a need to improve data systems and accountability mechanisms further in order to promote evidence-based decision-making, improve productivity, and benefit nutritional goals. Policy analysis in this area must disaggregate countries by income group to ensure correct advice is generated for the right set of countries. The paper therefore generates important insights related to investment, nutrition, productivity, mutual accountability and availability of data. Contrary to the sentiments that public investments in agricultural sectors are a waste, we call for an increase in public spending to the sector as it improves both the agriculture sector and health outcomes.